Impact of Nature-based Tourism on Earnings of Local People: Evidence from Keenjhar Lake in Pakistan (The Pakistan Development Review, 2015)
Nature-based tourism is the fastest growing part of tourism [Kuenzi and McNeely (2008)]. Wetland areas including lakes are an important source of nature-based tourism as tourists like their scenic views and enjoy doing different activities including swimming, canoeing, diving and learning about nature [van der Duim and Henkens (2007)]. Wetlands are amongst the most important ecosystems on Earth and provide numerous goods and services including recreational services [Mitsch and Gosselink (2007)]. Increasing demand for nature-based tourism has raised the importance of wetlands